Clinical laboratory diagnostics in dentistry: Application of microbiological methods - Claesson, Rolf; Johansson, Anders; Belibasakis, Georgios N. (Frontiers in Oral Health, 2022)
Diagnosis and treatment in dentistry are based on clinical examination of the patients. Given that the major oral diseases are of microbial biofilm etiology, it can be expected that performing microbiological analysis on samples collected from the patient could deliver supportive evidence to facilitate the decision-making process by the clinician. Applicable microbiological methods range from microscopy, to culture, to molecular techniques, which can be performed easily within dedicated laboratories proximal to the clinics, such as ones in academic dental institutions. Periodontal and endodontic infections, along with odontogenic abscesses, have been identified as conditions in which applied clinical microbiology may be beneficial for the patient. Administration of antimicrobial agents, backed by microbiological analysis, can yield more predictable treatment outcomes in refractory or early-occurring forms of periodontitis. Confirming a sterile root canal using a culture-negative sample during endodontic treatment may ensure the longevity of its outcome and prevent secondary infections. Susceptibility testing of samples obtained from odontogenic abscesses may facilitate the selection of the appropriate antimicrobial treatment to prevent further spread of the infection.